BIOSYNTHESIS OF COPPER OXIDE NANOPARTICLES USING Uraria picta (JACQ.) PLANT EXTRACT AND ITS CHARACTERIZATION - SHEIKH, SARTAJ; J. MUNGOLE, ARVIND; P. KANFADE, HARSHA; A. P. PAWAR; I. WARHADE, MRUNAL; BHANDAKKAR, SNEHAL; A. N. YERPUDE (The Bioscan, 2023)
The complete plant extract from Uraria picta was used in the current study as a natural reagent to synthesize CuO nanoparticles. A large part of the synthesis in response to the plant extract served as a reducing and stabilizing agent, resulting in copper oxide nanoparticles (NPs) of different sizes and forms. The synthesized nanoparticles were characterized using XRD, FTIR, UV-Vis spectroscopy, SEM and TEM. Strong absorbance peaks at 294 nm in the UV-visible spectrum are caused by the formation of CuO. The synthesized CuO XRD diffraction peaks closely matched those of the previously published CuO XRD. According to FTIR studies, the Cu-O bond stretching can be seen in the absorption bands at 515.50 cm-1 and 623.64 cm-1. The SEM micrographs show that the CuO particles are spherically formed, densely packed together, and irregularly dispersed. The TEM picture showed an average particle size of 50 nm. In this study, copper oxide nanoparticles of Uraria picta (JACQ.) plant extract prepared using the biosynthesis and characterized.